2006
DOI: 10.1086/502680
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Diagnosis of Empyema in Children: Comparative Evaluations by Culture, Polymerase Chain Reaction, and Pneumococcal Antigen Detection in Pleural Fluids

Abstract: Pneumococcal antigen detection in pleural fluid specimens from children provides a rapid and sensitive method of diagnosis of pneumococcal empyema, which can be confirmed by specific pneumolysin PCR when culture results are negative. Broad-range 16S rDNA PCR has value in detecting bacterial agents responsible for culture-negative pleural empyema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
109
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 28 publications
16
109
1
3
Order By: Relevance
“…21 In addition, nucleic acid amplification through polymerase chain reaction (PCR) and antigen testing are indispensable tools in the detection of microorganisms in cases with PPE. 17,22 In a study conducted in Spain, pneumococci were detected in 79% of culture-positive and 84% of culture-negative samples using real-time PCR; almost 50% were serotype 1. 4 Le Monnier et al 17 found that the sensitivity and specificity of the latex antigen detection in PPE were 90% and 95%, respectively.…”
Section: Microbiologymentioning
confidence: 99%
“…21 In addition, nucleic acid amplification through polymerase chain reaction (PCR) and antigen testing are indispensable tools in the detection of microorganisms in cases with PPE. 17,22 In a study conducted in Spain, pneumococci were detected in 79% of culture-positive and 84% of culture-negative samples using real-time PCR; almost 50% were serotype 1. 4 Le Monnier et al 17 found that the sensitivity and specificity of the latex antigen detection in PPE were 90% and 95%, respectively.…”
Section: Microbiologymentioning
confidence: 99%
“…23 However, microbiological cultures may produce false negatives for several reasons: small sample volume, slow growing bacteria, uncommon phenotypes, previous antibiotic therapy or inadequate conditions of transport and storage. 16,24 The main purpose of obtaining intraoperative samples for microbiological cultures in appendicitis was to identify, whether pathogens resistant to empirical antibiotics were present. Foo and colleagues collected data from more than 600 cases of acute appendicitis, demonstrating that less than 20 cultures grew resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] In pleural empyema, RT-PCR played an important role identifying pathogens in those patients with no culture growth, who had followed a previous antibiotic course. 15,16 Similar results were available for microbiological diagnosis in spontaneous bacterial peritonitis where RT-PCR increased the efficacy of cultures: RT-PCR detected pathogen in nearly all the patients with positive culture, and RT-PCR resulted positive in half of the patients with negative cultures. 17 Although molecular diagnosis cannot be considered as a replacement method in the clinical setting, there is an increasing awareness of the benefits, which may derive from the combined use of molecular analyses and conventional microbiology to optimize the research of pathogens.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations